VENTURE FINANCING OF START-UPS: A MODEL OF CONTRACT BETWEEN VC FUND AND ENTREPRENEUR - Osintsev, Yury (Economic Annals, 2010)
Venture capital has become one of the main sources of innovation in the modern, global economy. It is not just a substitute for bank loans: it has proven to be a more efficient way of financing projects at different stages. On one hand, venture financing allows for projects with higher risk, which leads to the possibility of higher returns on investment. On the other hand, venture investors who usually have managerial experience often participate in governing the business, which certainly adds value to the enterprise. In this paper we establish the model of contract between the venture capital fund and the entrepreneur, focusing on probably the most important issue of this contract: the shares of the parties in the business. The shares in the company determine the distribution of the joint surplus. The expected joint profits are not just exogenously specified in the contract but are dependent on the behavioural variables of both parties at the stage of fulfilling the contract. We call the behavioural variable of the entrepreneur ‘effort’ and the one of the venture fund ‘advice’. The probability of the project’s success, and hence the expected joint revenues, are increased by these two. However, both kinds of effort are costly to the respective parties that have made them. Based on this fact we can elaborate the profit functions of both sides of the contract. Our model can be considered as a basis for specifying contracts concerning venture financing. It can provide the logic for how the equilibrium shares of entrepreneur and venture fund are obtained.